Hydroxyethyl starch 130/0.4 (6%) and succinylated gelatine (4%) interfere with refractometry in dogs with haemorrhagic shock. (September 2019) - Yam, Elodie; Boyd, Corrin J.; Hosgood, Giselle; Claus, Melissa A.; Raisis, Anthea L.; Sharp, Claire R.; Smart, Lisa
Abstract: Objective: To determine if low molecular weight synthetic colloid fluids administered to dogs interfere with refractometric estimates of total plasma protein (TPPr) and urine osmolality (UOsm). Study design: Experimental study. Animals: Eighteen healthy Greyhound dogs. Methods: Anaesthetized Greyhounds subjected to haemorrhage for 60 minutes were given 80 mL kg –1 of Plasma-Lyte 148 (CRYST), or 20 mL kg –1 of hydroxyethyl starch 130/0.4 (HES) or succinylated gelatine (GELO) ( n  = 6 per group) intravenously over 20 minutes. Refractometric (TPPr) and biuret total plasma protein (TPPb) were measured before haemorrhage (Baseline), at end of shock (Shock), immediately (T20), then 40 minutes (T60), 100 minutes (T120) and 160 minutes (T180) after fluid administration. Urine specific gravity (USG) and UOsm were measured at all time points except T20. Estimated UOsm (eUOsm) was calculated from USG. Bias and limits of agreement (LOA) for TPPr versus TPPb, and eUOsm versus UOsm were calculated at each time point. Results: For dogs given CRYST and GELO, median TPPr and TPPb decreased in parallel, with a small consistent TPP bias (CRYST range of bias, 0.38−0.67 g dL –1 ; GELO range of bias, 0.42−0.58 g dL –1 ). Dogs given HES showed divergence between median TPPr and TPPb after T20, with a peak bias at T20 of 1.62 g dL –1 (LOA 1.29−1.95). Dogs given HES and GELO had markedly increased USG [HES peak median USG at T180 of 1.119 (Q1−Q3 1.103−1.122); GELO peak median USG at T120 of 1.114 (Q1−Q3 1.082−1.119)], with large increases in bias between eUOsm and UOsm [HES peak bias at T60 of 2995 mOsm kg –1 (LOA 2032−3958 mOsm kg –1 ); GELO peak bias at T120 of 2465 mOsm kg –1 (LOA 940−3990 mOsm kg –1 )]. Conclusions and clinical relevance: Administration of HES and GELO to dogs with haemorrhagic shock interferes with refractometric measurements for at least 3 hours after administration.